IMPLEMENTASI PENGGUNAAN MEDIA FLASH CARD PADA MATA PELAJARAN IPS DI KELAS IV SD NEGERI 1 TRIRENGGO BANTUL - Muhammad Sofirin; Abdul Rahim; Khotim Hanifudin Najib (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Analysis of the Use of Flash Card Media in Social Studies Subject for Fourth Grade at SD Negeri 1 Trirenggo Bantul. The main issue in this research is that the practice of implementing flash card media has not been specifically identified in terms of what the fourth-grade teacher does in Social Studies learning. The purpose of this study is to describe: 1) the planning, 2) the implementation of Social Studies learning using flash card media, and 3) students' responses to the use of flash card learning media in fourth-grade Social Studies at SD Trirenggo Bantul. The research method used is qualitative. Data collection techniques included interviews, observations, and documentation. Data analysis was carried out through: 1) Data reduction, 2) Data presentation, and 3) Drawing conclusions and verification. The results of the study show that: 1) The teacher has designed the flash card media in the teaching module and prepared the flash cards according to the material, 2) The learning implementation involved the use of flash card media through cooperative and presentation methods, 3) The students showed enthusiastic and joyful responses during the Social Studies learning process.